Questões ambientais, socioeconômicas e histórias de vida de assentados/as rurais do assentamento Estrela da Ilha no município de Ilha Solteira - SP - Simonato, Danitielle Cineli (2013)
The present study aimed to know the socioeconomic, environmental profile and life history of the rural settlers of the Estrela da Ilha settlement, in the municipality of Ilha Solteira, located in the State of São Paulo. The settlement has 209 land lots and the research was performed with 35 families. For data collection was used a questionnaire containing 50 questions about the socioeconomic and environmental profile of the settled families and, also, the collection of oral statements about the settlers' life history. The data analysis was made in a qualitative and quantitative way: the open questions were analyzed using the discursive textual analysis and the closed questions through simple statistics. The results pointed that the settlement profile in relation to age 37% are between 40-50 years, being 60% from male gender, the source of income of 54% of the families comes from their own property, the family income of 51% of the settlers is two minimum wages monthly, 68% has only uncompleted primary education, the home conditions indicated that 94% of the settlers have masonry dwellings and 89% of them are unfinished, 71% of the settlers claim to consume industrialized food frequently, the settlement production is characterized by dairy farming in most lots, followed by horticulture, the commercialization is done through cooperatives and associations, as well as sales in the city fairs. Was also researched, the environmental questions like the forest reserve area, water supply in 94% of the lots comes from wells, sanitary sewage 71% of the lots have septic tank, 74% of them use pesticide, was also researched about the solid waste management. The life histories highlighted the difficulties faced by the settlers to conquer the land, since the camp to the establishment on the lot. Denoted on the statements dreams, joys, settlers faith, it also disclosed the difficulties and problems of the Estrela da Ilha settlement. We conclude that in the community studied the biggest problems are related to socioeconomic issues, like income and education, and the worst environmental problems are the indiscriminate use of pesticides, the improper disposal of solid waste and the sanitary sewage. Therefore, these weaknesses need to be worked through public policies of access to education in rural areas, infrastructure, production and commercialization strategies and technical assistance for achieving sustainable rural development, emphasizing the quality of harmoniously living with the environment and social justice.